(untitled) (Biological Sciences - PJSIR, 1999)
Detailed mineralogical characteristics of the Chichali Formation glauconitic sandstone, as a possible source of K for crop production, weredetermined. It contained 66.8% sand (+50 urn), 19.6% silt (2-50 urn), 9.8% clay «2 urn) size fractions. The sand and silt fractions were composed of dominantly quartz and mica. As determined by the total K analysis, thesand had31% micaandthesilthad55%. Micaintheclaywasabout52% asindicated by total Kcontent. Also, the clay had 4% vermiculite and 11% smectite. Most clay particles were platy with difused boundaries. The interlayer spacehada repeatdistanceof 10.2 A asseenundertheTEMathighresolution.The study suggeststhatclay fraction is a disordered glauconite.The presence of about 25% kaoliniteindicates theK-deficient geo-chemical envi- ronment toward end of the glauconitization process.